2001
DOI: 10.1046/j.1469-8137.2001.00150.x
|View full text |Cite
|
Sign up to set email alerts
|

Receptor serine/threonine protein kinases in signalling: analysis of the erecta receptor‐like kinase of Arabidopsis thaliana

Abstract: SummaryThe Arabidopsis ERECTA (ER) gene regulates elongation of above-ground organs. ER encodes a member of the leucine-rich repeats-receptor-like protein kinases ( LRR-RLK) gene family, with the predicted protein containing a signal peptide, 20 leucine-rich repeats in the extracellular domain, a transmembrane domain, and a cytoplasmic serine/threonine protein kinase domain. The structural features of the predicted ER protein suggest its role in cell-cell signalling is through phosphorylating serine/threonine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 36 publications
2
63
0
Order By: Relevance
“…Other er mutant alleles did not show any significant effect on canalization; this suggests that either an alternate gene linked to ER is responsible for the effect or the presence of allele specificity in the modulation of developmental buffering. Variation in allelic effects of er mutants, however, is common and highly dependent on the phenotype measured, although er-105 has a consistently strong phenotypic effect (33,34,39,40). Moreover, the function of ER has also been shown to be dependent on genetic background (40).…”
Section: The Evolutionary and Quantitative Genetics Of Canalization Imentioning
confidence: 99%
“…Other er mutant alleles did not show any significant effect on canalization; this suggests that either an alternate gene linked to ER is responsible for the effect or the presence of allele specificity in the modulation of developmental buffering. Variation in allelic effects of er mutants, however, is common and highly dependent on the phenotype measured, although er-105 has a consistently strong phenotypic effect (33,34,39,40). Moreover, the function of ER has also been shown to be dependent on genetic background (40).…”
Section: The Evolutionary and Quantitative Genetics Of Canalization Imentioning
confidence: 99%
“…The pedicel elongates with the development of floral organs. Mutant screens for altered inflorescence branching patterns have revealed ER (Torii et al, 1996;Yokoyama et al, 1998;Lease et al, 2001a) and other genes (Lease et al, 2001b;Venglat et al, 2002). The commonly used Arabidopsis Ler ecotype harbors the er mutation, resulting in an altered inflorescence branching pattern caused by a reduction in the length of internodes and pedicels, the growth of clustered flowers at the apex of the inflorescence, and shorter, wider, and blunt-tipped siliques.…”
Section: Clv1 Can Function Outside Of the Meristemmentioning
confidence: 99%
“…These insertions are available as lines CS3954 and CS3955 from the ABRC. These two lines, originally in the Ws-2 background, were backcrossed to Ler, Ws-2 er-123 (Lease et al, 2001a), and Columbia er-106 (Lease et al, 2001a) for a comparative analysis of the effect of the mutation in both backgrounds.…”
Section: Clv1 and Clv3 Allelesmentioning
confidence: 99%
“…Masle et al, (2005) reported the isolation of a gene that regulates TE in A. thaliana, ERECTA. a putative leucine-rich repeat receptor-like kinase (LRR-RLK), known for its effects on inflorescence development (Torii et al, 1996;Lease et al, 2001) is a major contributor to a locus for Δ on the Arabidopsis chromosome 2, which, depending on growth conditions, explained 21-64% of the total phenotypic variation in Δ. Mechanisms include, but are not limited to, effects on stomatal density, epidermal cell expansion, mesophyll cell proliferation, and cell-cell contact. The alx8 mutant in A. thaliana is drought tolerant, exhibits improved water-use efficiency, and a number of drought-tolerance genes are up-regulated.…”
Section: Wue-related Gene Cloning and Identificationmentioning
confidence: 99%